PENGARUH PEWIWILAN DAN PUPUK PELENGKAP CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frustescens L.) - Nabilah, Inas; Yetti, Husna; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research can be done in the frequency of the pruning of water shoots and the concentration of liquid supplementary fertilizer and the best combination in improving growth and yield of cayenne pepper. The experimental method was conducted experiments in the form of a 4 x 4 factorial experiment arranged according to Complete Randomized Design. The first factor is the pruning of water shoots. The second factor of liquid supplementary fertilizer given in the form of Bayfolan. The data those collected analyze with Anova and Duncan’s new Multiple Range Test at the 5% level. Parameters observed were plant height, stem diameter, first flower appeared, the age of the first harvest, length of fruit, fruit diameter, weight per fruit, total fruit count per plant and weight of fruit per plant. The frequency of pruning of water shoots has no effect on all parameters, except for total fruit per plant. The frequency of pruning of water shoots 1 time indicates the total fruit count per plant more than the frequency of pruning of adventive shoots. PPC concentration has no effect on all parameters, except for the length of the fruit. A PPC concentration of 3 cc/l water indicates the length of the fruit is longer than the other PPC concentration. The interaction of frequency of pruning of adventive shoots and PPC concentration has no effect on all parameters. Keywords: Cayenne pepper, pruning of water shoots, liquid supplementary fertilizer